Sterols isolated from the sea urchin Diadema savignyi - Thao, Nguyen Phuong; Bach, Dang Ngoc; Thanh, Nguyen Van; Giang, Phan Minh; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Kim, Young Ho; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, six sterols namely cholest-6-ene-5α,8α-epidioxy-3β-ol (1), cholest-5-ene-3β,7α-diol (2), cholest-5-ene-3β,7β-diol (3), cholest-5-ene-7β-methoxy-3β-ol (4), cholest-5-ene-3β-ol (5), and cholest-5-ene-3β-sulfate sodium (6), were isolated from the methanol extract of the sea urchin Diadema savignyi. Their structures were elucidated by 1D- and 2D-NMR experiments and comparison of their NMR data with reported values. These compounds were isolated from D. savignyi for the first time.